PERUBAHAN POLA KEPEMIMPINAN PESANTREN DARUL HIDAYAH KECAMATAN RASAU JAYA KABUPATEN KUBU RAYA - Tukiman, Tukiman (JPMIS)
This thesis entitle : the Change of Pattern of Leadership Pesantren Darul Hidayah Subdistrict Rasau Jaya of Kubu Raya Regency". Pesantren, a traditional education institute typically Indonesia. This Research use the approach qualitative. because accurate problem represent the social symptom found on relation kyai, ustadz and santri from a lot of ethnical manner. Focus its solution is directional at relevant problem by respon is pesantren to modernism. Sosiologic-Anthropologic approach in very diffuse congeniality, specially model the Weberian, applied to analyse and interpret the existence, leadership, assess, and phenomenon pesantren and also various link of between religious factors, inclusive of opinion, the practice institute, social process and authority. Further solution in this thesis is aimed at by a question hit how pesantren take care of its autonomy, x'self identity, and spirit of his traditional when dealing with modern life influence, and also how pesantren anticipate the role sosial-budayanya in modern world context. Under consideration, this thesis pare about description of concerning leadership pesantren in contemporary context and its effort to make balance to the social change. In this case, its solution is relied on case of Change of Pattern of Leadership Pesantren Darul Hidayah Subdistrict Rasau Jaya of Kubu Raya Regency. Relevant Important Issue with the Change of Pattern of leadership pesantren in social transformation studied by: function pesantren as institute missionize, pesantren as " life school", pesantren as cultural custodian, pesantren as environment of spiritual and Sufism, and also social role of pesantren. Keyword: Leadership Kyai, pesantren, social role